2019
DOI: 10.1002/jimd.12055
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, neuroradiological, and biochemical features of SLC35A2‐CDG patients

Abstract: SLC35A2-CDG is caused by mutations in the X-linked SLC35A2 gene encoding the UDP-galactose transporter. SLC35A2 mutations lead to hypogalactosylation of Nglycans. SLC35A2-CDG is characterized by severe neurological symptoms and, in many patients, early-onset epileptic encephalopathy. In view of the diagnostic challenges, we studied the clinical, neuroradiological, and biochemical features of 15 patients (11 females and 4 males) with SLC35A2-CDG from various centers. We describe nine novel pathogenic variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 24 publications
1
36
0
Order By: Relevance
“…CDG‐0248 carried a novel missense variant c.818 G > A (p.Gly273Asp) that was absent from the mother, but the father was unavailable for testing. However, in a recent separate study on SLC35A2‐CDG, an unrelated affected individual was identified carrying the same c.818 G > A (p.Gly273Asp) as a de novo variant showing a slightly abnormal CDT (Vals et al, ; doi: https://doi.org/10.1002/jimd.12055) Two individuals from this paper (CDG‐0389, CDG‐0469) and the paper from Vals et al () are shared.…”
Section: Resultsmentioning
confidence: 74%
“…CDG‐0248 carried a novel missense variant c.818 G > A (p.Gly273Asp) that was absent from the mother, but the father was unavailable for testing. However, in a recent separate study on SLC35A2‐CDG, an unrelated affected individual was identified carrying the same c.818 G > A (p.Gly273Asp) as a de novo variant showing a slightly abnormal CDT (Vals et al, ; doi: https://doi.org/10.1002/jimd.12055) Two individuals from this paper (CDG‐0389, CDG‐0469) and the paper from Vals et al () are shared.…”
Section: Resultsmentioning
confidence: 74%
“…In a recent case series, Vals et al failed to see a correlation between the phenotype severity and the estimated quantity of pathogenic SLC35A2 variants. 5 Of interest in the current study, variant proportions did not correlate with the messenger RNA expression of the alternative allele, suggesting the possibility of a nonsense-mediated decay. Because the UGT protein was not assessed, relationship among the varied proportions of the alternative allele to UGT quantities or function remain unclear.…”
mentioning
confidence: 59%
“…N-glycosylation defects linked to pathogenic variants in the Solute Carrier Family 35 Member A2 gene (SLC35A2) have emerged as causal to an X-linked early onset epileptic encephalopathy typically manifested with infantile spasms or West syndrome in women or in mosaic men and most recently, they were also identified in approximately 30% of NAFE because of FCD type 1. 5,6 SLC35A2 encodes a uridine diphosphate galactose transporter (UGT). A defect in the UGT results in a reduced galactosylation of N-glycosylated proteins, glycosphingolipids, and proteoglycans, which affects neuronal migration, axon guidance, and synaptic physiology.…”
mentioning
confidence: 99%
“…Hypogalactosylation of transferrin is a reported marker of the genetic galactosylation deficiencies SLC35A2-CDG and B4GALT1-CDG [ 26 , 48 ], although SLC35A2-CDG has been reported to result in hypogalactosylation of transferrin N -glycans in only about half of the patients [ 49 , 50 ]. Here, we likewise observed reduced galactosylation for total plasma proteins and IgG connected to these diseases.…”
Section: Discussionmentioning
confidence: 99%